Patient recall of postoperative protocols following hand surgery does not differ by information provider: a randomized clinical trial - Dhruv Mendiratta; Rohan Singh; Aleksandra McGrath; Aleksandra McGrath (Frontiers in Surgery)
Understanding of postoperative care is limited in patients who undergo ambulatory surgery. This study compares patients' recall of information regarding postoperative self-care when being verbally informed by either a surgeon or assistant nurse postoperatively prior to discharge. Secondary objectives for this study are to compare differences in patients' level of “feeling that they understood the information”, stress, and satisfaction. A non-blinded randomized single-center controlled trial was conducted at a hand surgical unit in Northern Sweden (Trial Registration ID: NCT03893968). Patients were randomized into a control (surgeon) or intervention group (assistant nurse). Patients were asked seven questions about postoperative self-care one week postoperatively via telephone call, yielding a maximum score of seven points. Thirty-nine patients were informed by assistant nurses, and thirty-three patients were informed by surgeons. There was no difference in recall between the two groups (4.95 vs. 5.15, p = 0.5). Patients from both groups lacked knowledge on postoperative outcomes (41.0% vs. 42.4%). The mean scores for “feeling of having understood the information” (mean of 9.23 for patients informed by assistant nurses vs. mean of 9.45 for patients informed by surgeons) and satisfaction (9.69 vs. 9.45, respectively) was high, while mean scores for stress was low (1.38 vs. 1.18, respectively). Few patients answered all questions correctly: 8.3% of the patients answered all questions correctly, and 37.5% of the patients answered six or more questions correctly. The findings suggest that surgeons and assistant nurses are equally good at verbally informing patients regarding postoperative hand-surgical self-care. More effort is needed to make patients understand symptoms of postoperative infections.